2021
DOI: 10.1021/acs.analchem.1c00765
|View full text |Cite
|
Sign up to set email alerts
|

A One-Dimensional U-Net-Based Calibration-Transfer Method for Low-Field Nuclear Magnetic Resonance Signals

Abstract: The reconstruction of the statistical analysis model of an instrument is a time-consuming and expensive process. Herein, the feasibility of spectral model calibration-transfer application to the same type of low-field nuclear magnetic resonance (LF-NMR) instrument was investigated using a one-dimensional U-net (1D U-net). Unlike conventional calibration-transfer algorithms such as direct standardization (DS), the 1D U-net network can reduce the error between the master and slave instruments through iterative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The most recent one is less relevant for this study since it is based on time-domain NMR. 6 The second study successfully performed transfers of partial least squares (PLS) regressions between 43, 60, and 80 MHz benchtop NMR devices. 7 This study demonstrated the potential of calibration transfer between low-field 1 H NMR.…”
Section: Metrics and Morementioning
confidence: 99%
See 1 more Smart Citation
“…The most recent one is less relevant for this study since it is based on time-domain NMR. 6 The second study successfully performed transfers of partial least squares (PLS) regressions between 43, 60, and 80 MHz benchtop NMR devices. 7 This study demonstrated the potential of calibration transfer between low-field 1 H NMR.…”
Section: Metrics and Morementioning
confidence: 99%
“…Several studies have been devoted to calibration transfer between high-field NMR instruments. , However, until now, there have only been two studies investigating the feasibility of calibration transfer between low-field 1 H NMR. The most recent one is less relevant for this study since it is based on time-domain NMR . The second study successfully performed transfers of partial least squares (PLS) regressions between 43, 60, and 80 MHz benchtop NMR devices .…”
mentioning
confidence: 99%
“…Various methods were proposed for spectral data transfer from low-field to high-field NMR, which include direct standardization and piecewise direct standardization [42,43]. The possibility of NMR data transfer from a low field to a high field has also been investigated in time-domain NMR [44]. In addition, calibration transfer of low-field proton NMR ( 1 H-NMR) spectra using partial least squares regression in 40-, 60-, and 80-MHz benchtop NMR has been investigated [45].…”
Section: Introductionmentioning
confidence: 99%